1998
DOI: 10.1021/jm950802i
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Long Chain Alkyl Acyl Carnitine Esters. Potentially Biodegradable Cationic Lipids for Use in Gene Delivery

Abstract: A series of alkyl acyl carnitine esters (alkyl 3-acyloxy-4-trimethylammonium butyrate chloride) were synthesized as potential biocompatible cationic lipids for use in gene transfer. The physicochemical properties of the lipids, liposomes prepared from them, and their complexes with DNA were characterized by differential scanning calorimetry (DSC), particle size, zeta potential, and surface monolayer measurements. The transition temperatures and behavior at an air-water interface for this series are similar to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
80
1

Year Published

2002
2002
2010
2010

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 116 publications
(82 citation statements)
references
References 31 publications
1
80
1
Order By: Relevance
“…Transfection efficiency of the CCLA-based liposome with reporter genes It has been reported that different helper lipids 23 and the charge ratio of the positively charged lipid versus negatively charged DNA 24 can contribute to the variable transfection efficiency. To determine the optimal combination for the CCLA-based liposome transfection, two most commonly used helper lipids, cholesterol and DOPE, were formulated with CCLA at different molar ratio and screened for their transfection efficiency in vitro using b-gal reporter gene assay.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Transfection efficiency of the CCLA-based liposome with reporter genes It has been reported that different helper lipids 23 and the charge ratio of the positively charged lipid versus negatively charged DNA 24 can contribute to the variable transfection efficiency. To determine the optimal combination for the CCLA-based liposome transfection, two most commonly used helper lipids, cholesterol and DOPE, were formulated with CCLA at different molar ratio and screened for their transfection efficiency in vitro using b-gal reporter gene assay.…”
Section: Resultsmentioning
confidence: 99%
“…Gene transfection has also been demonstrated with several monovalent cationic liposomes with molar ratio of cationic lipid to helper lipid close to 1:1. 1,23,25 CCLA has four hydrophobic chains and two positive charges, a structure resembling to two singly charged cationic lipids conjugated together. Therefore, the optimal molar ratio of CCLA to DOPE (1:2) is comparable to the ratio of 1:1 for other cationic and helper lipids.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other viral types have revealed toxicity or caused devastating immune and inflammatory responses, resulting in patient death. [7][8][9] Because of these problems, alternative methods involving the development of synthetic materials are currently being studied for the delivery of nucleic acids. [10][11][12][13][14][15] Systems that mimic the positive features of viral delivery vehicles yet circumvent the negative aspects of these systems are highly sought-after.…”
Section: Introductionmentioning
confidence: 99%
“…We and others have previously shown that lungs can be preferentially and efficiently transfected following i.v. administration of a transgene expression plasmid complexed with cationic liposomes (28)(29)(30)(31)(32). Pulmonary gene transfer via cationic lipids is largely mediated by a passive mechanism of serum-induced aggregation of lipid vectors, although the nonspecific interaction of cationic lipid vectors with the negatively charged endothelium may also play a role (33).…”
Section: Cationic Lipid-mediated Pulmonary Gene Transfermentioning
confidence: 99%